The Relationship between Learning Concentration and Student Emotional Maturity to Mathematics Learning Outcomes of Class X Students of High School - Narsih Narsih; Baso Intang Sappaile; Nasrullah Nasrullah (PT Mattawang Mediatama Solution, 2022)
This study was conducted to determine the relationship between learning concentration and student emotional maturity to mathematics learning outcomes of class X high school students. This study is an ex-post facto study with a research sample of 205 students selected using the stratified cluster random sampling technique. The instruments used are a learning concentration questionnaire, a student emotional maturity questionnaire and a mathematics learning outcomes test. The data from the study were analyzed by descriptive statistical analysis and inferential statistics with multiple linear regression analysis. The results showed that students' learning concentration and emotional maturity are in the high category and students' mathematics learning outcomes are in the moderate category, learning concentration and student emotional maturity have a joint relationship with mathematics learning outcomes of class X high school students, learning concentration has a positive relationship with mathematics learning outcomes of class X high school students, student emotional maturity has a positive relationship with mathematics learning outcomes a student of class X high school.